Nuclear Factor Erythroid 2 Regulates Human HSC Self-Renewal and T Cell Differentiation by Preventing NOTCH1 Activation - Alessandro Di Tullio; Diana Passaro; Kevin Rouault-Pierre; Sukhveer Purewal; Dominique Bonnet (Stem Cell Reports, 2017)
Nuclear factor erythroid-derived 2 (NF-E2) has been associated with megakaryocyte maturation and platelet production. Recently, an increased in NF-E2 activity has been implicated in myeloproliferative neoplasms. Here, we investigate the role of NF-E2 in normal human hematopoiesis. Knockdown of NF-E2 in the hematopoietic stem and progenitor cells (HSPCs) not only reduced the formation of megakaryocytes but also drastically impaired hematopoietic stem cell activity, decreasing human engraftment in immunodeficient (NSG) mice. This phenotype is likely to be related to both increased cell proliferation (p21-mediated) and reduced Notch1 protein expression, which favors HSPC differentiation over self-renewal. Strikingly, although NF-E2 silencing in HSPCs did not affect their myeloid and B cell differentiation in vivo, it almost abrogated T cell production in primary hosts, as confirmed by in vitro studies. This effect is at least partly due to Notch1 downregulation in NF-E2-silenced HSPCs. Together these data reveal that NF-E2 is an important driver of human hematopoietic stem cell maintenance and T lineage differentiation.